-4n-27=-7(-1+3n)

Simple and best practice solution for -4n-27=-7(-1+3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n-27=-7(-1+3n) equation:


Simplifying
-4n + -27 = -7(-1 + 3n)

Reorder the terms:
-27 + -4n = -7(-1 + 3n)
-27 + -4n = (-1 * -7 + 3n * -7)
-27 + -4n = (7 + -21n)

Solving
-27 + -4n = 7 + -21n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '21n' to each side of the equation.
-27 + -4n + 21n = 7 + -21n + 21n

Combine like terms: -4n + 21n = 17n
-27 + 17n = 7 + -21n + 21n

Combine like terms: -21n + 21n = 0
-27 + 17n = 7 + 0
-27 + 17n = 7

Add '27' to each side of the equation.
-27 + 27 + 17n = 7 + 27

Combine like terms: -27 + 27 = 0
0 + 17n = 7 + 27
17n = 7 + 27

Combine like terms: 7 + 27 = 34
17n = 34

Divide each side by '17'.
n = 2

Simplifying
n = 2

See similar equations:

| 3n+6=4 | | 8h+9=81 | | x+2=2-6 | | 6.88x+27.52=55.04 | | 5y+10(y-9)+25(y+4)=590 | | 8(0.3)-0.5=y | | -7n+26=-3(1+5n)+8n+29 | | lg(x-2)=2 | | 10%2+6=x | | 5(y+3)=7(y-5) | | 9x^2+4=-17 | | b^2-b-14=-8 | | Logx+log(x-2)=log(3) | | 4(x-1)+68=-4x | | 2x^2=16-4 | | 3x^2+x^3=x^4 | | v^2+3v-1=-3 | | Ln(6x-5)+ln(x-1)=(5) | | 35-5x=5(1-7x) | | 4(x-6)+15=-41 | | 9x^2+3x^3=3x^4 | | 6+9/6n=60 | | 5w^2-24w-5=0 | | s-15=15.37 | | -15-7n-3n=-n-6n | | 5x+10y=-30 | | 9x+18y-4z=-1 | | y=0.13x+18.76 | | -5(p+6)+3p=-33-2p | | n^2+4n+9=6 | | 40x+25y=150 | | -18=36-27v |

Equations solver categories